Competition in bank-provided payment services - Wilko Bolt; David Humphrey (European Central Bank (ECB), 2013)
Banks supply payment services that underpin the smooth operation of the economy. To ensure an efficient payment system, it is important to maintain competition among payment service providers but data available to gauge the degree of competition are quite limited. We propose and implement a frontierbased method to assess relative competition in bank-provided payment services. Billion dollar banks account for around ninety percent of assets in the US and those with around to billion in assets turn out to be both the most and the least competitive in payment services, not the very largest banks.
Keywords: G21; L80; L00; 330; banks; competition; frontier analysis; payments; Zahlungsverkehr; Bankgeschäft; Finanzintermediation; Wettbewerb; Wirkungsanalyse; Technische Effizienz; USA